MENINGKATKAN INOVASI PEREKONOMIAN MARITIM DALAM PENGENDALIAN INFLASI - Roslia, Roslia; Mokodompit, Eliyanti Agus (Jurnal Multidisipliner Kapalamada, 2025)
This study aims to analyze how innovation in the maritime sector can serve as an effective strategy for controlling inflation in Indonesia. Using a quantitative descriptive approach and macroeconomic data from the maritime sector during the period 2018–2022, the research examines the relationship between logistics efficiency, sea transportation costs, port performance, fuel prices, and innovation investment on inflation levels. The results indicate that innovations such as supply chain digitalization, the use of renewable energy, and the development of smart ports contribute to improved logistics efficiency and reduced operational costs, thereby helping to mitigate inflation. However, the impact of innovation investment tends to manifest over the long term and requires consistent policy support. The study recommends that the government accelerate technological transformation in the maritime sector, strengthen international cooperation, and provide incentives for the development of green energy and port digitalization. With the right strategy, the maritime sector has the potential to become a key instrument in ensuring price stability and promoting sustainable economic growth.